An Agricultural Land Resource Assessment Study Based on GIS—An Example from Guiyang City - 刘建军 李春来 等 (Acta geochimica, 2002)
This paper assesses the agricultural land resources of Guiyang City by means of GIS,on the basis of the pressure-state-response model in which soil heavy metal contamination is selected as a pressure indicatror.he results suggest that most of the agricultural land resources are of good quality,However,there are 17.11km^2 dry land and paddy field,which belong to the region of serious heavy metal contamination and are not fit for planting crops.At the same time,the high quality plowland,which is suitable for cultivation,has decreased nearly by 1/3 due to soil heavy metal contamination.These findings may improve our understanding that it is very important to prevent and cure heavy metal contamination of Guiyang City.